THORACIC CT-SCAN WITH EGFR MUTATIONS IN PULMONARY ADENOCARCINOMA PATIENTS WITH PULMONARY METASTASES AT DR. MOEWARDI HOSPITAL, SURAKARTA, INDONESIA - Viska Wahyu Arianti; Widiastuti Soewondo; Sulistiyani Kusumaningrum; Muhammad Lukman Hermansyah; Yusup Subagio Sutanto; Hari Wujoso (Majalah Biomorfologi, 2023)
Highlights The thoracic CT scan can be an alternative evaluation before administering EGFR-targeting medicine to patients. EGFR is now a therapeutic target for lung cancer. Â  Abstract Background: EGFR mutation is one of the molecular markers associated with prognosis and therapy in lung adenocarcinoma patients, including with lung metastases. The predominant imaging modality for assessing lung cancer is a chest CT scan, which correlates with prognosis. Objective: This study aimed to explore the association between characteristics of lung adenocarcinoma based on chest CT-Scan and EGFR mutation in lung adenocarcinoma with lung metastases. Material and Method: This study involved 65 lung adenocarcinoma patients in Dr. Moewardi Hospital, Surakarta, Indonesia, from January 2018-December 2020. Result: Chest CT-Scan and EGFR mutation were assessed in all subjects. EGFR mutation was found in 32 (49.8%) subjects. The risk of EGFR mutation was found to be higher in patients with lung adenocarcinoma who had lung metastases in a peripheral location (OR=11.56; 95%CI 3.57-37.33; p<0.001), tumor size <4 cm (OR=8.00; 95%CI 2.64-24.22; p<0.001), and semi-solid density (OR=5.21; 95%CI 1.79-15.19; p=0.002). Conclusion: EGFR mutation is associated with tumor location, size, and thickness based on chest CT-Scan in lung adenocarcinoma with lung metastases patients.